Uncollected cycles of A. I. Kuprin: the Easter cycle - Соценко, Наталия Федоровна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
In the article is considered of the secondary (reader's) cycle, consisting of ten stories written by Kuprin within thirty three years. By the context of this Easter cycle testifying to a genre experiment of the author the means of communication and traced between works allowing to consider them a cycle are established. It is noted that in a cycle are formed mini-cycles and each work of this cycle is capable to enter intertextual communications with other works of Kuprin. The originality of cycles of Kuprin connected with the main style reception of the author – an avtointertekstualnost is specified.